Development of VNTR-Based Test System for V. cholerae Typing - Ya. A. Kibirev; I. V. Darmov; M. A. Loginova; I. V. Marakulin; D. A. Chukhlantsev; T. I. Dormidontova; S. L. Kuznetsov; A. V. Kuznetsovskii (Проблемы особо опасных инфекций, 2011)
Analysis of VNTRs was used for typing of V. cholerae strains deposited in microbial culture collection of 48 Central Research Institute. The most informative loci and flanking primers were chosen, VNTR profiles were compiled, and allele variability analysis of the strains was carried out. Laboratory series of test system were manufactured . The developed test system can be used for epidemiological monitoring and investigations, as well as for passportization of collection strains.